PENGARUH HEDONIC SHOPPING MOTIVATION, PRICE DISCOUNT, DAN VISUAL MERCHANDISING TERHADAP IMPULSE BUYING DI UNIQLO INDONESIA - Sitindaon, Desmond Hamonangan; Hussein, Ananda Sabil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
This study aims to determine the effect of hedonic shopping motivation,price discount and visual merchandising on impulse buying in UNIQLO Indonesia in Tangerang. This type of research is explanatory research which explains the causal relationship between variables through testing hypotheses with quantitative analysis methods. This study uses a sample of 140 respondents taken from the UNIQLO consumer population of Tangerang. Sampling using purposive sampling technique. The sample characteristics chosen were, at least 17 years old and maximum 25 years old, consumer of UNIQLO, and had carried out impulse buying at UNIQLO. The test tool used to test the instrument of this study is multiple linear regression analysis which is supported by validity test, reliability test, classical assumption test. Hypothesis testing is done using the t-test using the SPSS 26.0 program. From the results of the study, it can be concluded that the variables hedonic shopping motivation, price discount, and promotion have a significat influence on the impulse buying of UNIQLO in Tangerang.